A Review on Impact of Environmental Conditions on Fishing Net Mechanical Properties - Halim, Nur Aini Binti; Siti Zaharah Kunchi Mon (Progress in Engineering Application and Technology, 2021)
Fishing industry organization needs a good knowledge of the manufacturer of fishing net. Fishers need the experience to catch the fish, and the importance of this knowledge may sustain their family’s resources. Increasing demand for food sources such as protein has forced the fisherman to increase the catch. The fisherman must make sure that the fishing net has strong weathering resistance and excellent strength. This research investigates the breaking strength and tensile strength of Polyamide (PA) netting twines, biodegradable fishing nets and polyethylene netting twine under the exposure of environmental conditions and artificial conditions such as UV light, seawater, xenon arc lamp and soil. Also, changes in the fishing net surface were reviewed to observed the effect before and after exposure to the environmental conditions. As a consequence of breaking strength, it can be generalized that the most abrasive condition that will degrade the fishing net is sunlight. The result from this research expected to help the fishing industries produce high-quality fishing net, which is to resist weathering conditions.